Increasing Access to Safe Abortion Services Through Auxiliary Nurse Midwives Trained as Skilled Birth Attendants - K C, N P; Basnett, I; Sharma, S K; Bhusal, C L; Parajuli, R R; Anderson, K L (Kathmandu University Medical Journal, 2012)
Background The use of medical abortion methods was approved by Department of Health Services in 2009 and introduced in hospitals and a few primary health centres (PHCs). Access would increase if services were available at health post level and provided by auxiliary nurse midwives trained as skilled birth attendants. Evidence from South Africa, Bangladesh, Nepal and Vietnam show that mid-level health workers can provide medical abortion safely. Objectives To determine the best way to implement the new strategies of medical abortion into the existing health system of Nepal; and to facilitateits full-scale implementation, monitoring and evaluation. Methods An implementation research involving a baseline study, implementation phase and end line study was done in ten districts covering five development regions from July 2010 to June 2011. Both qualitative and quantitative methods were used. Results Of 1,799 medical abortion clients who received service, 46% were disadvantaged Janjati, 14% were Dalit, 42% were upper caste groups and rest were advantaged Janjati (7%), Muslim (1%) and others. 14% were referred by female community health volunteers and 56% were referred by others. Complication rate of 0.3% was well below acceptable levels. Condom use increased from 8% to 28% by the end of study. Use of Pills, Depo, intra uterine devices and Implants also increased, but use of long acting family planning methods was negligible. Conclusions This model should be replicated nationwide at health posts and sub-health posts where auxiliary nurse milwifes are available 24 hours/day. Focus should be given first to those areas where access is difficult, time consuming and costly. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6341 Kathmandu Univ Med J 2011;9(4):260-66